Depression among people living in rural and urban areas of Thailand: A cross-sectional study - Wiriya Mahikul; Wisut Lamlertthon; Kanchana Ngaosuwan; Pawaree Nonthasaen; Napat Srisermphoak; Wares Chancharoen; Saimai Chatree; Arpaporn Arnamwong; Pisinee Narayam; Chatchamon Wandeecharassri; Pakin Wongpanawiroj (PLoS ONE, 2025)
Background Depression has a growing trend in the population worldwide. In this cross-sectional study, we investigated the prevalence and associated factors of depression among individuals residing in rural (Ban Luang district, Nan Province) and urban (Lak Si, Bangkok) areas of Thailand. Understanding the differences in depression between these two settings can provide insights for specific targeted interventions and mental health policies. Methods The multistage stratified random sampling was applied to select the study participants. We recruited participants from rural and urban communities in Thailand using a structured survey questionnaire through either face-to-face interviews or in paper or electronic form. We collected data on depression using the Patient Health Questionnaire-9 (PHQ-9) tool and sociodemographic characteristics and conducted descriptive statistics and logistic regression analysis. Results Of 867 survey participants, 420 were from rural areas (Nan) and 447 were from urban areas (Bangkok). Participants’ mean age was 55.9±9.5 years in rural areas and 56.0±12.0 years in urban areas. Most participants in urban areas were women, married, and had lower education levels (71.1%, 50.3%, 58.8%, respectively). The overall prevalence of depression across both settings was 18.6%. We found a higher prevalence of depression in the urban (31.8%) than the rural (4.5%) setting. In multiple logistic regression analysis, urban residence was significantly associated with higher rates of depression compared with rural residence (adjusted odds ratio [AOR] 9.43, 95% confidence interval [CI] 5.08–17.52). Nuclear family and using social media were associated with lower levels of depression in urban areas (AOR 0.50 and 0.43, 95% CI 0.27–0.93 and 0.22–0.84, respectively). Higher education level was significantly associated with higher levels of depression in rural areas (AOR 3.84, 95% CI 1.19–12.42). Conclusion This study emphasized the difference in depression and related factors between rural and urban areas of Thailand, highlighting a greater prevalence in urban areas. To help prevent depression, it is important to address specific challenges in each setting, such as those faced by highly educated individuals living in rural areas with high depression rates, exploring social media use patterns in urban populations, and understanding dynamics of the nuclear family. Our findings can inform the development of public health policies aimed at effectively mitigating the burden of depression and improving overall mental well-being in specific settings.